Mid-Term Appraisal of Ninth Five Year Plan (1997-2002) Government of Goa - Planning Commission (Planning Commission, 1999)
The Ninth Five Year Plan envisaged to make Goa a modern welfare State with high growth rate, all round human resource development and ecologically sustainable industry. in order to achieve this goal, Approach to the Ninth Five Year Plan was finalised keeping in view the priorities of the Government, recommendations of the State Planning Board and experience of Eighth Five Year Plan of the State.
Directorate of Planning, Statistics and Evaluation, Government of Goa